Arab Socialism and Ecumenical Tendencies in Egypt 1962–1970. Issue 4 (1st October 2016) - Merhavy, Menahem
Abstract: During the 1960s in Egypt, a group of intellectuals and publicists with left-leaning tendencies sought to base their socialist views on Islamic principles by reading early Islamic history as a repository of heroes and villains to fit their model of Arab socialist society. Beyond political aggrandizement of Nasserism, this article claims that these intellectuals described Islam as socialist, which led them in unexpected directions. First and foremost, such study led several to make surprising claims regarding the leaders of early Islam that ipso facto brought them closer to the Shiʿi view of this formative period of Islam. Rather than merely translating socialism into Islamic terminology, these scholars imbued early Islamic history with fresh and revolutionary meaning. The process of making Islam more relevant to twentieth-century Muslims meant re-examining age-old rivalries, which had the potential to change the relations between Sunni and Shiʿi Islam dramatically.